The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14020892
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Patenting within Containerized Liner Shipping

Abstract: Increasingly, in many industries, companies commercialize their technology and innovations through patenting to gain an edge over competition. Within the maritime sector, while literature on innovation is expanding, issues related to the importance of intangible assets, such as patenting, for the participant firms of the industry remain unaddressed. Utilizing innovational frameworks and patent data withdrawn from European Patent Organization’s (EPO’s) database, the aim of this paper is to investigate the innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…This questionnaire was distributed to employees of globally renowned shipping companies, yielding the primary influencing factors on the international competitiveness of ports from the perspective of shipping enterprises [14]. Constantinos Chlomoudis et al concluded that enhancing innovation capabilities, as evidenced by patents and other innovative strengths of liner shipping companies, is a crucial pathway to improving corporate competitiveness [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This questionnaire was distributed to employees of globally renowned shipping companies, yielding the primary influencing factors on the international competitiveness of ports from the perspective of shipping enterprises [14]. Constantinos Chlomoudis et al concluded that enhancing innovation capabilities, as evidenced by patents and other innovative strengths of liner shipping companies, is a crucial pathway to improving corporate competitiveness [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research conducted so far focuses on several research areas, such as ship power systems [60] analysed from several distinct perspectives, including, without limitation, the perspective of technological competitiveness of ship integrated power system enterprises [61] or the trends and development of those systems in China [62]. Other studies seek solutions to such research problems as the assessment of patent activity of liner shipping companies [63], technological competitiveness of enterprises [61], corporate sustainability (in a broad sense) in shipping companies [64] and autonomous ships [65,66]. None of the papers referred to above examines the technologies or applications for the mitigation or adaptation against climate change in the maritime industry.…”
Section: Building Knowledge Based On Patent Analysismentioning
confidence: 99%